Pain self-efficacy questionnaire and its use in samples with different pain duration time - Maroco, J. P. (2019)
BACKGROUND AND OBJECTIVES: The pain self-efficacy questionnaire has been frequently used in several languages, but its use is limited to chronic pain. This study aimed to i) evaluate the properties of the pain self-efficacy questionnaire among Brazilians with different durations of pain occurrence; ii) present a new proposal for estimation of the overall self-efficacy belief score; and iii) compare such score among different pain duration time. METHODS: A total of 1,155 adults (79.0% women; 38.6±10.8 years) participated, 337 had no pain, 386 reported pain for less than 3 months, 253 reported pain for more than 3 months with a recurrent pattern, and 179 reported continuous pain for more than 3 months. The confirmatory factor analysis was performed to check the pain self-efficacy questionnaire unifactorial model good-fit. The pain self-efficacy questionnaire invariance was tested in independent samples using multigroup analysis. We proposed the calculation of the self-efficacy belief score from the factor score obtained in the confirmatory factor analysis. The score was compared among groups (ANOVA, alpha=5%). RESULTS: After inserting four correlations between errors of items, the pain self-efficacy questionnaire model shows to be fit to the sample (X2/df=7.059; CFI=0.978; GFI=0.964; RMSEA= 0.072). The model was invariant between independent samples. Lower self-efficacy belief was found among participants with pain for less than three months (p<0.05).CONCLUSION: There is evidence of a relationship between the self-efficacy belief and the pain characteristics, where the presence of pain and length of time living with pain might be important factors in the study of the concepts involved in the perceptions of pain and self-efficacy.